Syncretism of Confucianism, Buddhism and Daoism in Liaozhai Zhiyi in Terms of Filial Piety - Wang, Aiqing (Center for Research and Development of Religious Literature and Heritage, 2021)
Liáozhāi Zhìyìis one of the representative compilations in the genre ofzhìguài‘strange writing’ during the Qing (1644-1912) era, and it conveys filial piety through narration and authorial commentary. This researchscrutinizesnarratives regardingthe preponderant construal of filial piety, so as toexplore the harmonious contemporaneous of religious thinking and behavior in Qing China. This researchconductsinterpretative and hermeneutic research on four narratives in Liáozhāi Zhìyì, namely,XíFāngpíng, LèZhòng, SìshíQiān, and QiánbǔWū, and also refersto classic treatises regarding filial piety. Given the fact that narratives in Liáozhāi Zhìyìthemed by or appertaining to filial pietyentail elements of three religions simultaneously.This studypropoundsthat itilluminates amalgamation of Confucianism, Buddhism and Daoism, i.e.sānjiàohéyī, in seventeenth-century China.